If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7 = 5 + 2(x + -8) Reorder the terms: -7 + 3x = 5 + 2(x + -8) Reorder the terms: -7 + 3x = 5 + 2(-8 + x) -7 + 3x = 5 + (-8 * 2 + x * 2) -7 + 3x = 5 + (-16 + 2x) Combine like terms: 5 + -16 = -11 -7 + 3x = -11 + 2x Solving -7 + 3x = -11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -7 + 3x + -2x = -11 + 2x + -2x Combine like terms: 3x + -2x = 1x -7 + 1x = -11 + 2x + -2x Combine like terms: 2x + -2x = 0 -7 + 1x = -11 + 0 -7 + 1x = -11 Add '7' to each side of the equation. -7 + 7 + 1x = -11 + 7 Combine like terms: -7 + 7 = 0 0 + 1x = -11 + 7 1x = -11 + 7 Combine like terms: -11 + 7 = -4 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| 8v^2-20=0 | | 22/7÷7/3 | | 5y+7=77 | | 20x-16=164 | | X*8x=96 | | X+16=-2x-3 | | 9(x-7)=5(x-3) | | X*8x= | | Z/4-5=1 | | (P+q)2= | | 6p+4r-5p+2r= | | 24=n/6 | | F/5-3=2 | | -1+2(2x-3)=-5x-16 | | 9(x-7)+5=2x-9 | | 22=(10x)+4 | | 16-3t=4 | | 4(c-d)= | | 10q+8q-136=68-8q | | G/4-1=3 | | 3x^3-243x=0 | | 4(x-7)+5=2x-9 | | (cotx)(sinx)= | | 8x+7=37+3x | | 3yx+3yx= | | 10q+8q-136=34-8q | | 12-12x=3x^2 | | 18v-18v= | | -204=-12v | | 8(9x-9)+7=7 | | 10q+8q-136=34-8x | | 58=x*2x |